pН-sensitive edible films based on the sodium caseinate/agaragar biocomposite - M. V. Novikova; K. E. Viroline; A. D. Nefyodov; M. V. Uspenskaya (Пищевые системы)
In the modern world, shelf life extension of foods with a possibility of controlling their freshness and quality in real time is gaining increasing importance. To solve this task, the development of pH-sensitive films based on edible biopolymers with addition of anthocyans as a color indicator can be proposed. For this experiment, sodium caseinate/ agar-agar biocomposite films with different content of anthocyans from black carrot (Scorconera hispanica) in a range of 0 to 15 mass% in increments of 5 mass% were prepared. It was established that the anthocyan content did not affect the thickness and moisture content of the films; however, it significantly reduced their moisture absorption and transparence. Water vapor permeability of the biocomposite films increased with an increase in the content of the aqueous extract of anthocyans from black carrot, which can be linked with the formation of pores and microcracks in the biocomposite matrix. All films with anthocyans showed changes in color depending on the environmental pH, which intensities depended on the anthocyan content. Edible films based on the mixture of sodium caseinate and agar-agar can potentially be used in the food industry to determine freshness of foods, which spoilage results in pH changes.